Arbuscular mycorrhizal characterization associated with Uncaria guianensis and Uncaria tomentosa in Amazonian soils - Garzón , Lina Paola; Peña-Venegas, Clara Patricia (Revista de Ciencias Agrícolas, 2023)
There are some plant species with cultural and economic importance in the Amazon, such as Uncaria guianensis and U. tomentosa, both commonly named “cat’s claw”. Since these species grow in soils with low levels of organic matter and nutrients, both depend on arbuscular mycorrhizae to grow. The information about arbuscular mycorrhizal fungi communities for U. tomentosa is limited and there is no current research on U. guianensis. Therefore, this research provides additional information on the arbuscular mycorrhizal fungi communities associated with Uncaria species in Amazonian soils. Both the percentage of root colonization and the influence of the edaphic composition in the two species were determined.Also, the richness and diversity of arbuscular mycorrhizal fungi were assessed using the spore isolation method and also, through the molecular analysis of virtual taxa. In addition, the difference between the soils was analyzed. Although U. guianensis grows in both Oxisols and Alluvial Entisols and U. tomentosa is restricted to Oxisols, sporulation of AM and root colonization does not respond significantly to variations in soil chemical properties. Additionally, 72 virtual taxa were identified for Uncaria species (53 U. tomentosa and 19 U. guianensis) and the relative abundance of arbuscular mycorrhizal fungi was higher in roots of Uncaria species than in soils. The arbuscular mycorrhizal fungi community that colonizes the roots of Uncaria species indicates that these species behave as wild species; therefore, the ex-situ propagation of the species in agricultural systems could be less successful than forest enrichment.